The effect of monitoring committees on the relationship between board structure and firm performance - Aymen Ammari; Sarra Amdouni; Ahmed Zemzem; Abderrazak Ellouze (Journal of Risk and Financial Management, 2016)
The purpose of this study is to investigate the impact of board structure on the performance of French firms in the presence of several monitoring committees. We studied 80 publicly listed French firms spanning from 2001 to 2013. We concluded that large board size has a negative effect on market performance. While large board size in combination with the existence of at least three committees enhances accounting performance and does not have any impact on market performance, the existence of a board dominated by independent directors with the presence of at least three committees seems to have only a negative impact on accounting performance. Our findings indicate that monitoring committees are beneficial for shareholders only for corporations with a large board size.
Keywords: 650; board composition; monitoring committees; firm performance; France